Origins and Revolutions Human Identity in Earliest Prehistory - Gamble, Clive (Cambridge University Press, 2013)
It is a great pleasure to be able to record my thanks to the many people and institutions that have contributed towards this book. The award of a British Academy Research Readership was essential to enable both travel and reading and the time to rethink the questions of why agriculture happened and the appearance of people like ourselves. As important was the opportunity provided by Dr Julie Hansen, who invited me for a semester as a Visiting Professor to research and teach at the Department of Archaeology, Boston University, funded by a Humanities Foundation Fellowship. My seminar class at Boston were among the first to hear the ideas in this book and set me right on a number of points; Ben Vining, Susan Mentzer, Satoru Murata, Menaka Rodriguez, Rita Pelosi and Sophie Telgezter. I should also like to thank Curtis Runnells, Priscilla Murray and David Stone for all their hospitality and good conversation. Across the Charles River a special debt goes to the staff of the Tozzer library and to Ofer Bar-Yosef at the Peabody Museum, Harvard: his encouragement is infectious and his generosity with data and ideas helped this project immensely. Unexpected travel opportunities came through C5 and the filming of a documentary series ‘Where do we come from?’ broadcast in 2002. The production team of Michael Proudfoot, Jessica Whitehead, Jim Sayer and James Routh made light of remote destinations and in six months I saw more than I could have bargained for. I was also able to meet with many friends and make new ones both off and on camera. To all of them, thank you for your patience and your knowledge.